Evaluación del comportamiento de agentes biocidas en la eliminación de microorganismos en un tanque de almacenamiento de diésel (2018)
Diesel fuel in Colombia has undergone changes in recent years, due to the fact that it is looking for a product that is increasingly friendly to the environment. These changes have made it more susceptible to microbiological attack, which leads to the degradation of fuel properties, as well as the appearance of suspended solids, sludge and sludge. Finally, this translates into higher operating costs for service stations (EDS) due to tank drains and filter changes, as well as being at risk of affecting the engines or injection systems of the final customer and acquiring sanctions by the customer. Superintendence of Industry and Commerce. When making a diagnosis in 48 EDS at a national level, it was found that only 33% of the samples evaluated have a good appearance, 78% do not approve the established parameter of water and sediment content and 90% of the EDS have contamination microbiological Additionally, it was possible to demonstrate that there is a direct relationship between the water and sediment content of the sample and the presence of microorganisms.